Importância dos ensaios físico-químicos no controle de qualidade de vacinas - Maria P. Blanco; Cristiane Barata Silva; Santos A. Vicentini Neto; Lara M. Catarino; Ozeias de Lima Leitão; Elizabete P. Figuerêdo; Mateus H. M. Neves; Silvana C. Jacob; Lisia M. G. dos Santos (Química Nova)
The National Immunization Program (NIP), established in 1973, is recognized nationally and internationally as one of the largest vaccination programs in the world, integrated into the Unified Health System (SUS). Over the years, the NIP has faced challenges in vaccine quality control, leading to significant evolution, especially since 1983 when the National Institute of Quality Control in Health (INCQS) centralized this control. INCQS conducts biological, microbiological, and physicochemical assays, such as pH, appearance, aluminum content, and thiomersal, the latter present in multidose vaccines as a preservative. Retrospective analysis of physicochemical assays reveals variations in analysis quantities, often correlated with specific vaccination campaigns. The introduction of new vaccines in the NIP, such as the pentavalent and inactivated polio vaccines, impacted quality control. Regarding the pH and appearance of vaccines, assays demonstrate improvements over time, including the adoption of more sensitive and specific techniques. The implementation of visual inspection aspect analysis as a preventive measure after occurrences of unsatisfactory lots underscores the commitment to vaccine safety. Public laboratories, like INCQS, play a crucial role in this process, ensuring the safety of immunobiological for the entire Brazilian population. The current challenge lies in the need to keep up with technological advancements to maintain vaccine quality.